The university as a cultural actor in promoting students’ responsibility toward environmental sustainability: An environmental humanities perspective - Alfehaid, Khalid Abdulrahman; ALhuraybi, Fatimah Ali; Elagamy, Aida AbdElaal; Ibrahim, Ashraf Ragab (Research Journal in Advanced Humanities, 2026)
Responsibility toward environmental sustainability has become a central challenge for higher education institutions due to its direct impact on raising students' awareness and shaping their behaviors toward the environment. This study aims to assess the role of Prince Sattam bin Abdulaziz University in promoting responsibility toward environmental sustainability among students and to explore ways to enhance such role. The study followed the descriptive-analytical method. It relied on a structured questionnaire that included 362 male and female students from various colleges and academic levels. The questionnaire focused on four main dimensions: the role of the university administration, faculty staff members, academic courses, and student activities, in addition to a special section on ways to enhance environmental responsibility. The results showed that the university achieves a very high level in promoting responsibility toward environmental sustainability across all dimensions, with the role of faculty staff members and academic courses being the most influential on students' awareness and behavior, followed by student activities and university administration. Students emphasized the importance of integrating sustainability in curricula, organizing training programs and workshops, supporting innovative student initiatives, enhancing community partnerships, and utilizing digital technologies to raise environmental awareness. The study concluded that the integration of university policies and educational practices is a key factor in promoting responsibility toward environmental sustainability. It also emphasized the need to continuously develop programs and activities to ensure the consolidation of sustainable environmental behavior among students.